Coexisting With Different Human-Wildlife Coexistence Perspectives - Glikman, Jenny Anne; Frank, Beatrice; Ruppert, Kirstie A.; Knox, Jillian; Sponarski, Carly C.; Metcalf, Elizabeth Covelli; Metcalf, Alexander L.; Marchini, Silvio (Frontiers in Conservation Science, 2021)
Over the last decade, there has been a remarkable increase in scientific literature addressing human–wildlife interactions (HWI) and associated concepts, such as coexistence, tolerance, and acceptance. Despite increased attention, these terms are rarely defined or consistently applied across publications. Indeed, the meaning of these concepts, especially coexistence, is frequently assumed and left for the reader to interpret, making it hard to compare studies, test metrics, and build upon previous HWI research. To work toward a better understanding of these terms, we conducted two World Café sessions at international conferences in Namibia, Africa and Ontario, Canada. Here, we present the array of perspectives revealed in the workshops and build upon these results to describe the meaning of coexistence as currently applied by conservation scientists and practitioners. Although we focus on coexistence, it is imperative to understand the term in relation to tolerance and acceptance, as in many cases these latter terms are used to express, measure, or define coexistence. Drawing on these findings, we discuss whether a common definition of these terms is possible and how the conservation field might move toward clarifying and operationalizing the concept of human-wildlife coexistence.